Spread, Depth and Order Flow Patterns of Warrants and Their Underlying Stocks on the Stock Exchange of Thailand - Visaltanachoti, N. (Institutional Knowledge at Singapore Management University, 2004)
This study compared the trading characteristics of warrants and their underlying stocks. The Stock Exchange of Thailand provided a good platform for comparing the trading characteristics of warrants and their underlying stocks because both these securities are traded in the same market venue and have identical trading rules. Hence, the impact of trading protocol on intraday variation and an informed trader's decision to buy warrants or stocks was controlled. The paper found that they have a similar downward sloping pattern of spreads, adverse selection component, and liquidity immediacy, U-shaped for volatility and trading volume, and upward-sloping for depth and market order ratio. After controlling for the intraday patterns, spreads are positively associated with liquidity immediacy and negatively related to the market order ratio and total depth. The results indicate that the market structure does affect the intraday pattern of trading characteristics.